Close association of active nitrifiers with Beggiatoa mats covering deep‐sea hydrothermal sediments. (28th November 2013) - Winkel, Matthias; de Beer, Dirk; Lavik, Gaute; Peplies, Jörg; Mußmann, Marc
Summary Hydrothermal sediments in the Guaymas Basin are covered by microbial mats that are dominated by nitrate‐respiring and sulphide‐oxidizing Beggiatoa. The presence of these mats strongly correlates with sulphide‐ and ammonium‐rich fluids venting from the subsurface. Because ammonium and oxygen form opposed gradients at the sediment surface, we hypothesized that nitrification is an active process in these Beggiatoa mats. Using biogeochemical and molecular methods, we measured nitrification and determined the diversity and abundance of nitrifiers. Nitrification rates ranged from 74 to 605 μmol N l−1 mat day−1, which exceeded those previously measured in hydrothermal plumes and other deep‐sea habitats. Diversity and abundance analyses of archaeal and bacterial ammonia monooxygenase subunit A genes, archaeal 16S ribosomal RNA pyrotags and fluorescence in situ hybridization confirmed that ammonia‐ and nitrite‐oxidizing microorganisms were associated with Beggiatoa mats. Intriguingly, we observed cells of bacterial and potential thaumarchaeotal ammonia oxidizers attached to narrow, Beggiatoa‐like filaments. Such a close spatial coupling of nitrification and nitrate respiration in mats of large sulphur bacteria is novel and may facilitate mat‐internal cycling of nitrogen, thereby reducing loss of bioavailable nitrogen in deep‐sea sediments.